Reversible Computation : 8th International Conference, RC 2016, Bologna, Italy, July 7-8, 2016, Proceedings /: 8th International Conference, RC 2016, Bologna, Italy, July 7-8, 2016, Proceedings. (2016) - Unknown
No abstract available